A monograph of the genus Maladera Mulsant & Rey, 1871 of China (Coleoptera: Scarabaeidae: Melolonthinae: Sericini) - Fabrizi, Silvia; Liu, Wan-Gang; Bai, Ming; Yang, Xing-Ke; Ahrens, Dirk (Zootaxa, 2021)
In the present monograph, the taxonomy of the species of the genus Maladera Mulsant & Rey, 1871 from China is revised. We recorded 224 valid species for China, including 152 species new to science: Maladera allonitens Ahrens, Fabrizi & Liu, sp. n., M. anhuiensis Ahrens, Fabrizi & Liu, sp. n., M. apicalis Ahrens, Fabrizi & Liu, sp. n., M. aptera Ahrens, Fabrizi & Liu, sp. n., M. baii Ahrens, Fabrizi & Liu, sp. n., M. baishaoensis Ahrens, Fabrizi & Liu, sp. n., M. bansongchana Ahrens, Fabrizi & Liu, sp. n., M. baoxingensis Ahrens, Fabrizi & Liu, sp. n., M. bawanglingana Ahrens, Fabrizi & Liu, sp. n., M. bawanglingensis Ahrens, Fabrizi & Liu, sp. n., M. beibengensis Ahrens, Fabrizi & Liu, sp. n., M. beidouensis Ahrens, Fabrizi & Liu, sp. n., M. bikouensis Ahrens, Fabrizi & Liu, sp. n., M. breviclava Ahrens, Fabrizi & Liu, sp. n., M. bubengensis Ahrens, Fabrizi & Liu, sp. n., M. businskyorum Ahrens, Fabrizi & Liu, sp. n., M. chenzhouana Ahrens, Fabrizi & Liu, sp. n., M. constellata Ahrens, Fabrizi & Liu, sp. n., M. crenatotibialis Ahrens, Fabrizi & Liu, sp. n., M. crenolatipes Ahrens, Fabrizi & Liu, sp. n., M. daanensis Ahrens, Fabrizi & Liu, sp. n., M. dadongshanica Ahrens, Fabrizi & Liu, sp. n., M. dahongshanica Ahrens, Fabrizi & Liu, sp. n., M. dajuensis Ahrens, Fabrizi & Liu, sp. n., M. danfengensis Ahrens, Fabrizi & Liu, sp. n., M. dayaoshanica Ahrens, Fabrizi & Liu, sp. n., M. diaolinensis Ahrens, Fabrizi & Liu, sp. n., M. emeifengensis Ahrens, Fabrizi & Liu, sp. n., M. enigma Ahrens, Fabrizi & Liu, sp. n., M. erlangshanica Ahrens, Fabrizi & Liu, sp. n., M. eshanensis Ahrens, Fabrizi & Liu, sp. n., M. excisilabrata Ahrens, Fabrizi & Liu, sp. n., M. fangana Ahrens, Fabrizi & Liu, sp. n., M. fangchengensis Ahrens, Fabrizi & Liu, sp. n., M. fencli Ahrens, Fabrizi & Liu, sp. n., M. fengyangshanica Ahrens, Fabrizi & Liu, sp. n., M. fereobscurata Ahrens, Fabrizi & Liu, sp. n., M. filigraniforceps Ahrens, Fabrizi & Liu, sp. n., M. flavipennis Ahrens, Fabrizi & Liu, sp. n., M. fuanensis Ahrens, Fabrizi & Liu, sp. n., M. guangdongana Ahrens, Fabrizi & Liu, sp. n., M. guangzhaishanica Ahrens, Fabrizi & Liu, sp. n., M. guanxianensis Ahrens, Fabrizi & Liu, sp. n., M. guanxiensis Ahrens, Fabrizi & Liu, sp. n., M. guomenshanensis Ahrens, Fabrizi & Liu, sp. n., M. guomenshanica Ahrens, Fabrizi & Liu, sp. n., M. gusakovi Ahrens, Fabrizi & Liu, sp. n., M. haba Ahrens, Fabrizi & Liu, sp. n., M. habashanensis Ahrens, Fabrizi & Liu, sp. n., M. hajeki Ahrens, Fabrizi & Liu, sp. n., M. hansmalickyi Ahrens, Fabrizi & Liu, sp. n., M. hongyuanensis Ahrens, Fabrizi & Liu, sp. n., M. houzhenziensis Ahrens, Fabrizi & Liu, sp. n., M. hsui Ahrens, Fabrizi & Liu, sp. n., M. huanianensis Ahrens, Fabrizi & Liu, sp. n., M. hubeiensis Ahrens, Fabrizi & Liu, sp. n., M. hui Ahrens, Fabrizi & Liu, sp. n., M. hunanensis Ahrens, Fabrizi & Liu, sp. n., M. hunuguensis Ahrens, Fabrizi & Liu, sp. n., M. hutiaoensis Ahrens, Fabrizi & Liu, sp. n., M. jaroslavi Ahrens, Fabrizi & Liu, sp. n., M. jatuai Ahrens, Fabrizi & Liu, sp. n., M. jiangi Ahrens, Fabrizi & Liu, sp. n., M. jingdongensis Ahrens, Fabrizi & Liu, sp. n., M. jinggangshanica Ahrens, Fabrizi & Liu, sp. n., M. jinghongensis Ahrens, Fabrizi & Liu, sp. n., M. jiucailingensis Ahrens, Fabrizi & Liu, sp. n., M. jizuana Ahrens, Fabrizi & Liu, sp. n., M. juntongi Ahrens, Fabrizi & Liu, sp. n., M. juxianensis Ahrens, Fabrizi & Liu, sp. n., M. kalawensis Ahrens, Fabrizi & Liu, sp. n., M. kryschanowskii Ahrens, Fabrizi & Liu, sp. n., M. kubeceki Ahrens, Fabrizi & Liu, sp. n., M. laocaiensis Ahrens, Fabrizi & Liu, sp. n., M. lianxianensis Ahrens, Fabrizi & Liu, sp. n., M. liaochengensis Ahrens, Fabrizi & Liu, sp. n., M. liwenzhui Ahrens, Fabrizi & Liu, sp. n., M. longruiensis Ahrens, Fabrizi & Liu, sp. n., M. luoxiangensis Ahrens, Fabrizi & Liu, sp. n., M. lushanensis Ahrens, Fabrizi & Liu, sp. n., M. lushuiensis Ahrens, Fabrizi & Liu, sp. n., M. maguanensis Ahrens, Fabrizi & Liu, sp. n., M. maoershana Ahrens, Fabrizi & Liu, sp. n., M. mupingensis Ahrens, Fabrizi & Liu, sp. n., M. nabanensis Ahrens, Fabrizi & Liu, sp. n., M. nanlingensis Ahrens, Fabrizi & Liu, sp. n., M. nanpingensis Ahrens, Fabrizi & Liu, sp. n., M. ninglangensis Ahrens, Fabrizi & Liu, sp. n., M. panyuensis Ahrens, Fabrizi & Liu, sp. n., M. parabrunnescens Ahrens, Fabrizi & Liu, sp. n., M. paradetersa Ahrens, Fabrizi & Liu, sp. n., M. paranitens Ahrens, Fabrizi & Liu, sp. n., M. paraserripes Ahrens, Fabrizi & Liu, sp. n., M. parobscurata Ahrens, Fabrizi & Liu, sp. n., M. peregoi Ahrens, Fabrizi & Liu, sp. n., M. pieli Ahrens, Fabrizi & Liu, sp. n., M. pingchuanensis Ahrens, Fabrizi & Liu, sp. n., M. pseudoconsularis Ahrens, Fabrizi & Liu, sp. n., M. pseudoegregia Ahrens, Fabrizi & Liu, sp. n., M. pseudoexima Ahrens, Fabrizi & Liu, sp. n., M. pseudofuscipes Ahrens, Fabrizi & Liu, sp. n., M. pseudonitens Ahrens, Fabrizi & Liu, sp. n., M. pseudosenta Ahrens, Fabrizi & Liu, sp. n., M. pui Ahrens, Fabrizi & Liu, sp. n., M. putaodiensis Ahrens, Fabrizi & Liu, sp. n., M. qianqingtangensis Ahrens, Fabrizi & Liu, sp. n., M. queinneci Ahrens, Fabrizi & Liu, sp. n., M. riberai Ahrens, Fabrizi & Liu, sp. n., M. robustula Ahrens, Fabrizi & Liu, sp. n., M. rubriventris Ahrens, Fabrizi & Liu, sp. n., M. rufonitida Ahrens, Fabrizi & Liu, sp. n., M. rufopaca Ahrens, Fabrizi & Liu, sp. n., M. sanqingshanica Ahrens, Fabrizi & Liu, sp. n., M. serratiforceps Ahrens, Fabrizi & Liu, sp. n., M. shaluishanica Ahrens, Fabrizi & Liu, sp. n., M. shangraoensis Ahrens, Fabrizi & Liu, sp. n., M. shaowuensis Ahrens, Fabrizi & Liu, sp. n., M. shenglongi Ahrens, Fabrizi & Liu, sp. n., M. shengqiaoae Ahrens, Fabrizi & Liu, sp. n., M. shiniushanensis Ahrens, Fabrizi & Liu, sp. n., M. shiruguanensis Ahrens, Fabrizi & Liu, sp. n., M. shiwandashanensis Ahrens, Fabrizi & Liu, sp. n., M. shoumanensis Ahrens, Fabrizi & Liu, sp. n., M. sinobiloba Ahrens, Fabrizi & Liu, sp. n., M. snizeki Ahrens, Fabrizi & Liu, sp. n., M. songi Ahrens, Fabrizi & Liu, sp. n., M. taiyangheensis Ahrens, Fabrizi & Liu, sp. n., M. tengchongensis Ahrens, Fabrizi & Liu, sp. n., M. tiachiensis Ahrens, Fabrizi & Liu, sp. n., M. tiammushanica Ahrens, Fabrizi & Liu, sp. n., M. tiani Ahrens, Fabrizi & Liu, sp. n., M. tianzushanica Ahrens, Fabrizi & Liu, sp. n., M. tongzhongensis Ahrens, Fabrizi & Liu, sp. n., M. trifidiforceps Ahrens, Fabrizi & Liu, sp. n., M. uncipenis Ahrens, Fabrizi & Liu, sp. n., M. wandingana Ahrens, Fabrizi & Liu, sp. n., M. weni Ahrens, Fabrizi & Liu, sp. n., M. wipfleri Ahrens, Fabrizi & Liu, sp. n., M. wulaoshanica Ahrens, Fabrizi & Liu, sp. n., M. wuliangshanensis Ahrens, Fabrizi & Liu, sp. n., M. wupingensis Ahrens, Fabrizi & Liu, sp. n., M. xingkei Ahrens, Fabrizi & Liu, sp. n., M. xingkeyangi Ahrens, Fabrizi & Liu, sp. n., M. xinqiaoensis Ahrens, Fabrizi & Liu, sp. n., M. xuezhongi Ahrens, Fabrizi & Liu, sp. n., M. yakouensis Ahrens, Fabrizi & Liu, sp. n., M. yangi Ahrens, Fabrizi & Liu, sp. n., M. yibini Ahrens, Fabrizi & Liu, sp. n., M. yipinglangensis Ahrens, Fabrizi & Liu, sp. n., M. yongrenensis Ahrens, Fabrizi & Liu, sp. n., M. yunnanica Ahrens, Fabrizi & Liu, sp. n., M. zhejiangensis Ahrens, Fabrizi & Liu, sp. n. The work also resulted in nine new combinations and 17 new synonyms: Maladera (subgenus Omaladera Reitter, 1896) (= Cephaloserica Brenske, 1900, syn. n.; = Coronoserica Brenske, 1902, syn. n.); Maladera formosae (Brenske, 1898) (= Autoserica castanea Arrow, 1913, syn. n.; = Serica korgei Petrovitz, 1967, syn. n.); Maladera motschulskyi (Brenske, 1897) (= Autoserica furcillata Brenske, 1897, syn. n.; Serica schoenfeldti Murayama, 1937, syn. n.); Maladera pallida (Burmeister, 1855) comb. n. (= Maladera ludipennis Miyake, Yamaguchi & Aoki 2002, syn. n.); Maladera renardi (Ballion, 1870) (= Serica delicta Brenske, 1897, syn. n.); Maladera secreta (Brenske, 1897) (= Autoserica cruralis Frey, 1972, syn. n.); Maladera verticalis (Fairmaire, 1888) (= Autoserica hiekei Frey, 1972, syn. n.); Maladera futschauana (Brenske, 1897) (= Autoserica atavana Brenske, 1902, syn. n.; = Autoserica montivaga Moser, 1915, syn. n.); Maladera aureola (Murayama, 1938) (= Maladera liotibia Nomura, 1974, syn. n.); Maladera brunnescens (Frey, 1972) comb. n., Maladera exima (Arrow, 1946) comb. n., Maladera gansuensis (Miyake & Yamaya, 2001) comb. n., Maladera nigrobrunnea (Moser, 1926) comb. n., Maladera orientalis (Motschulsky, 1858) (= Serica salebrosa Brenske, 1897, syn. n.; =Autoserica davidis Brenske, 1898, syn. n.; = Serica mirabilis Brenske, 1894, syn. n.), Maladera punctulata (Frey, 1972) comb. n., Maladera rotunda (Arrow, 1946) comb. n., Maladera serripes (Moser, 1915) comb. n., Maladera senta (Brenske, 1897) (= Autoserica subspinosa Brenske, 1898, syn n.); Maladera spissigrada (Brenske, 1897) (= Serica nakayamai Murayama, 1938, syn. n.); Maladera tibialis (Brenske, 1898) comb. n. The lectotypes of the following species were designated: Autoserica furcillata Brenske, 1897, A. cariniceps Moser, 1915, A. diversipes Moser, 1915, A. flammea Brenske, 1898, A. fuscipes Moser, 1915, A. gibbiventris Brenske, 1897, A. hongkongica Brenske, 1898, A. obscurata Moser, 1915, A. piceola Moser, 1915, Serica delicta Brenske, 1897, S. exigua Brenske, 1894, S. nigrobrunnea Moser, 1926, S. orientalis Motschulsky, 1858, S. pallida Burmeister, 1855, S. salebrosa Brenske, 1897, and S. sibirica Brenske, 1897. Keys to the subgenera and species groups of Maladera, as well as a key to the species within each species-group are provided. Furthermore, we provide maps of the species distribution, as well as illustrations of the habitus and male genitalia.